Exploring the risk of glycemic variability in non-diabetic depressive individuals: a cross-sectional GlyDep pilot study - Mishra, Shivang; Singh, Anurag Kumar; Rajotiya, Sumit; Singh, Pratima; Raj, Preeti; Bareth, Hemant; Singh, Mahaveer; Jagawat, Tushar; Nathiya, Deepak; Tomar, Balvir Singh (Frontiers in Psychiatry, 2023)
The data regarding glycemic variability and depression in non-diabetic patients are scarce. The glycemic variability associated with increased cardiovascular risk can be a missing link in patients with depression.Methods: This single-centric pilot study involved FGM (Flash glucose monitoring) Abbott Libre Pro to evaluate the glycemic variability. We assessed the depression by CES-D (Center for epidemiological studies-Depression). We divided the patients into two groups based on their CES-D score (score ≥33 and score <33). We calculated various glycemic variability indices like HBGI (High blood glucose index), CONGA (Continuous overlapping net glycemic action), ADDR (Average daily risk ratio), MAGE (Mean amplitude of glycemic excursion), MAG (Mean absolute glucose), LI (Lability index), J-Index using EasyGV version 9.0 software. Data analysis was done with SPSSv28.We screened patients with depression visiting the department of psychiatry, FGM was inserted in eligible patients of both the groups which yielded a data of 196 patient-days (98 patient-days for CES-D≥33 and 98 patient-days for CES-D<33). The glycemic variability indices CONGA (mg/dl), [76.48 ± 11.9 mg/dl vs. 65.08 ± 7.12 mg/dl] (p= 0.048), MAGE (mg/dl) [262.50 ± 25.65 vs. 227.54 ± 17.72] (p= 0.012), MODD (mg/dl) [18.59 ± 2.77 vs. 13.14 ± 2.39] (p= 0.002), MAG(mg/dl) [92.07 ± 6.24vs. 63.86 ± 9.38] (p= <0.001) were found to be significantly higher in the CES-D ≥33 group.Patients with more severe depressive symptoms, as suggested by CES-D≥ 33, had higher glycemic variability.